Histochemical Test of root, petiole and leaf of Kelembak (Rheum officinale Baill.) - Nurhasanah Nurhasanah; Dyah Iriani (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2021)
Kelembak (Rheum officinale Baill.) is perennial shrub with pharmacological activities, and well-known as one of traditional herbal medicine used widely in the world. The phytochemical study, as well as histochemical test, is pivotal to determine the potency of herbs used for disease treatment. Based on its secondary metabolite content.ÃÂ Histochemical test of R.officinale vegetative organs had not been reported. This study aims to determine the content of compounds in the vegetative organs of kelembak and provide information on the anatomical position of each compound in root, petiole and leaf. The preparation of histochemical test used freehand section method. Each sample was made in three replications for this test. A total of four secondary metabolites were examined in this study, i.e. alkaloid, tannin, lipid and flavonoid. The positive content of each compound was indicated by the coloration change. The specimens were then observed and photographed using light microscope.ÃÂ The results showed that the root, petiole and leaf showed positive content of alkaloids, tannins, lipids and flavonoids. However, the anatomical position of each secondary metabolites are different among root, petiole and leaf. The results of this study provide the first information of histochemistry vegetative organs of Rheum officinale.